Pengaruh Modernisasi Terhadap Minat Belajar Pendidikan Islam: Perspektif Pelajar Setingkat SMA dan Sederajat Di Kota Pare Kabupaten Kediri - umar umar (LPPM IAI Hasanuddin Pare-Kediri, 2015)
This study discusses about how much influence the modernization of the interest in learning Islamic education for high school students / equivalent, how the process of modernization in Pare occur, and how to face the symptoms modernisasi strategies in learning Islamic education. The author uses a mixture of qualitative research methods and quantitative, statistical calculation using SPSS20 for windows. The process of modernization in Pare caused by urbanization and immigration, as well as social change that intersect with modern traditions. Urbanization and immigration was originally motivated by the policy of the Dutch government to enliven the city. Strategi in the face of modernization to conduct religious activities that are traditional, solid instill religious knowledge, as well as maintaining a good old culture and are still relevant. The findings of this study indicate the level of modernization of high school students / equivalent in Pare very high with the number 3.2970 with a standard deviation of 1.96509 while interest in studying Islamic education average of 2.2228 with a standard deviation of 1.39825. It can be shown from the students who access the Internet on average 18 hours per week it just means they use the Internet 2:57 hours every day or every 1 hour they will take the time 10.7 minutes, this is a testament to the high level of modernization and also high interest in learning Islamic education.